Aplikasi Motif Piring Enamel Menggunakan Teknik Shibori dan Ecoprint pada Ready To Wear Deluxe - Audia Seftiani; Haidarsyah Dwi Albahi; Djuniwarti Djuniwarti (Jurusan Seni Rupa ISBI Bandung, 2025)
The textile industry in Indonesia is increasing along with the demand for various textile products that follow fashion trends, and the processing process produces waste. One of them is liquid waste in the form of residual dyes/synthetic liquids from the fabric dyeing process. Reducing liquid waste in the form of textile dyes can be done by reusing natural materials as textile dyes and making motifs, such as using the Shibori and Ecoprint techniques. This technique can create various beautiful motifs, one of which is the enamel plate motif. Making enamel plates as the main motif, as a form of preserving antique/vintage items in line with the fashion style that will be made. The design takes inspiration from objects around it, namely from patterns found on enamel plates, which is an example of how designs from the household world are applied in the fashion world as unique and attractive display innovations. This method of creating fashion works has stages such as; 1) exploration, 2) design, and 3) realization. The results of this creative work process are 6 (six) ready to wear deluxe looks which were presented at the Jogja Fashion Parade 2024. Through the creation of this work, it is hoped that it can add to the collection of innovative fashion works in the fashion world.